Human vascular endothelial cells reduce sphingosylphosphorylcholine-induced smooth muscle cell contraction in co-culture system through integrin β4 and Fyn - Ge Di; Meng Ning; Su Le; Zhang Yun; Zhang Shang-li; Miao Jun-ying; Zhao Jing (Acta Pharmacologica Sinica; Vol 33, No 1 (January 2012): Acta Pharmacologica Sinica, 2016)
Aim: In vascular strips, the adjacent endothelial cells modulate the contraction of vascular smooth muscle cells (VSMCs) induced by sphingosylphosphorylcholine (SPC) through nitric oxide (NO). The aim of this study was to elucidate the mechanisms by which vascular endothelial cells (VECs) reduce the SPC-induced contraction of VSMCs in a co-culture system. Methods: Human umbilical VECs and VSMCs were co-cultured. The VECs were transfected with integrin β4- or Fyn-specific siRNA. The areas of VSMCs that are involved in cell contractility were quantified using the Leica confocal software and collagen contractility assay. The production of NO in VECs was measured in the cell supernatants using NO Detection Kit. The levels of integrin β4 and Fyn in VECs and the levels of Rho kinase (ROCK) in VSMC were detected using immunofluorescence assays or Western blots. Results: Co-culture with VECs reduced the contraction of VSMCs induced by SPC (30 μmol/L). The down-regulation of integrin β4 or Fyn in VECs by the specific siRNA (20 nmol/L) was able to counteract the effects of VECs on the SPC-induced VSMC contractions. Furthermore, the integrin β4-specific siRNA (20 and 40 nmol/L) significantly reduced the level of Fyn protein and the production of NO in VECs, while increased the level of ROCK in VSMCs that had been stimulated by SPC. Conclusion: The VECs reduced the SPC-induced contraction of VSMCs in the co-culture system through integrin β4 and Fyn proteins. In this process, NO may be the factor downstream of integrin β4 in VECs, while ROCK may be the key protein regulating the contraction of VSMCs.